Engineering Adsorption Case for Efficient Capture of VOCs Using Biomass‐based Corncobs via a Carbonized Strategy. Issue 29 (4th August 2020) - Shen, Xuhua; Ou, Rui; Lu, Yutong; Yuan, Aihua; Liu, Jianfeng; Hu, Xiaocai; Yang, Zhen; Yang, Fu
Abstract: Herein, we report excellent corncobs‐derived carbon adsorbent by the special KOH chemical activation method which specific to selective adsorption removal of volatile organic chemicals (VOCs) under humid conditions. The obtained corncobs‐derived carbon adsorbent affords the enhanced adsorption removal capacities for volatile benzene (851.3 mg g ‐1 ) and toluene (854.9 mg g ‐1 ), outperforming comparative that derived from KOH grind means, which are 3 times higher than those of commercial activated‐carbon (benzene 275 mg g ‐1, toluene 310.5 mg g ‐1 ). We also demonstrated that the optimized structural property of the fabricated adsorbent had a good correlation with the adsorption efficiency of VOCs. Besides, the adsorption selectivity of benzene and toluene under different relative humidity distinguished by DIH (Difference of the Isosteric Heat) equation further indicates the beforehand adsorption behavior of toluene on the corncobs‐derived carbon adsorbent compared to benzene, which should be benefited from the improved synthetic tactics. Our study provides a real possibility for the practical engineering application of waste biomass (corncobs)‐derived engineering carbonaceous adsorbent in VOCs pollution control. Abstract : We reported an appreciable engineering carbonaceous absorbent derived from corncob, which affords outstanding adsorption property (>800 mg g −1 ) and high thermal‐stability (600 °C) in the engineering application for selective capturing polluted VOCs.